Pendekatan Terintegrasi OEE dan FMEA dalam Meningkatkan Keandalan Mesin Giling Kedelai pada Proses Produksi Tahu - poniman, Poniman; Musa , Akmal; Cahyono Putra, Andika (Fakultas Teknik UMRI, 2025)
This study explores the enhancement of soybean grinding machine reliability in tofu production by integrating Overall Equipment Effectiveness (OEE) and Failure Mode and Effects Analysis (FMEA). Conducted at CV. Restu Mulia Jaya between November 2024 and April 2025, the research utilized quantitative analysis of machine operational data. The findings revealed consistently low OEE values (39.04%–46.03%), attributed primarily to frequent downtime and variable performance rates. Equipment failures and speed losses were identified as the main sources of inefficiency. FMEA highlighted critical failure modes, notably clogged or corroded spirals and damaged filters. Recommended improvements include the adoption of Total Productive Maintenance (TPM), operator training, real-time monitoring, and the use of durable materials for key components. This integrated OEE-FMEA approach effectively prioritizes corrective actions and supports sustainable reliability improvement for soybean grinding machines in small-scale tofu production. Keywords: machine reliability, OEE, FMEA, tofu production, maintenance